HUBUNGAN PENGGUNAAN DAN PENANGANAN PESTISIDA PADA PETANI BAWANG MERAH TERHADAP RESIDU PESTISIDA DALAM TANAH DI LAHAN PERTANIAN DESA WANASARI KECAMATAN WANASARI KABUPATEN BREBES - Regita Damayanti Saputri; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Excessive use of pesticides causing pollution and environmental damage agriculture. Examination in Brebes on 31 samples of fruits and vegetables, found 22% of samples contain detectable residues of organophosphate and found two soil samples (10%) contained residues organochlorin. The purpose of this study was to determine the relationship of the use and handling of pesticides on their onion farmers against pesticide residues in the soil on agricultural land Wanasari Village, District Wanasari, Brebes. This study is observational method with cross sectional approach. The population in this study were all farmers in the Wanasari conducting spraying. Collecting data using the tool Banu questionnaire and examination of pesticide residues in soil using GC-MS Gas Chromatography - Mass Spectrometry. The results of this study are of 55 69.1 onion farmers use pesticides are not good. The use of pesticides covering 80% is not good in mixing pesticides, 87.3% use a smaller dose, 49.1% use pesticides that are not registered with the Ministry of Agriculture, 87.3% is not good in the way of spraying and 87.3 does well in frequency spraying. Handling pesticides in agricultural land is not good 59.1%, ie 74.5% is not good in handling pesticide containers, 90.9% is not good in storage of pesticides, 89.1% is not good in handling a spill and 87.3% did not either in place to clean pesticide containers. The research result is negative soil samples pesticide residues. The conclusion was that no pesticide residue class organochlorin.